Digital Healthcare : is a Trend or Necessity? - Kristina Dewi, I Gusti Ayu Agung; Mahyuni, Luh Putu (Department of Public Health, Faculty of Sport Science, Universitas Negeri Semarang, 2024)
In the era of digital advancement, the government is actively endorsing different digital health apps. This trend is particularly noticeable in Indonesia, where consumer-focused eHealth services have gained extensive approval. The acceptance of these services has risen significantly over time, propelling Indonesia to a global ranking of third place in using health apps. This research intends to determine whether the inclination towards digital healthcare is genuinely embraced as a necessity, or if it’s just a passing trend. The study involves conducting a nationwide quantitative investigation across Indonesia among 418 users of mobile health apps, based on the UTAUT 2 theory which was modified according to research needs by adding variable FOMO. Data collection through online surveys and uses structural equation modeling (SEM-PLS), to assess the connections between these factors. They reveal that digital healthcare is not only embraced but also perceived as a necessity. While necessity-driven motivation remains dominant, the study also uncovers hedonic factors playing a role. This combination of necessity and trend-related aspects underscores the potential market for digital healthcare. The outcomes of this research bring promising news for developers of digital healthcare solutions. It reveals that there is a genuine demand and need for digital healthcare services.